في أعداد ونشاط الفطريات والبكتريا في التربة Carbaryl 10D تأثير المبيد الحشري - حسن هذيلي, كاظم; غازي نغيمش, رزاق; خلف الياسري, مهدي (University of Thi-Qar Journal of Science, 2011)
A field and laboratories studies were carried out through 2008/2009 season todetermine the effect of the insecticide Carbaryl 10D (which was spraying on palms to protectfrom Batrachedra amydrala) on the number and activity of fungi and bacteria in soil. Thefirst study was conducted in seven palm orchards in Soq-Elshyookh / Thi-qar government byspraying 15 kgs from carbaryl 10D in two split application to six of these orchards. After 3and 16 days, the number of fungi and bacteria in soil were determined and compared withtheir numbers before spraying . The insecticide didn't affect fungi and bacteria numbers justin one state from six through the first three days and in the later days the numbers increased slightly.In the second and third study, the insecticide was mixed with soil in the levels ( 0 , 20, 40 , 60 , 80 and 100 ) mg. kg -1 . A significant decrease was happened in the numbers offungi and bacteria which reached 26 and 18.9 % respectively when using the insecticide inlevel 100 ) mg. kg -1 . Also there was a significant decrease in the microbial activity in thefirst days of incubation which was determined by measuring the quantity of CO2 released ,the decreasing percentage was 14 and 21.9 % respectively when using the insecticide in level100 ) mg. kg -1 .After the eighth day of incubation , the numbers of fungi and bacteria andtheir activity began to increase .